Customary law and the government of Africans in South Africa in the transition to a unitary state - Costa, Anthony (My University, 1998)
'The way in which white has governed black in South Africa during approximately the past century', formed the focus of Edgar Brookes's History of Native Policy published in 1924.' Over the years, colonialism, segregation and apartheid have served as alternative labels for 'native policy', purported answers to the question 'What is the appropriate manner in which to govern Africans?' Responses to this question, and the particular role of customary law, form the subject of this paper, and its argument that by the end of the nineteenth century, the ground had been laid, in the Cape and Natal, for the recognition of African forms of government, including customary law, a development which may be located in the philosophies of indirect rule and liberalism. Africans were to be governed by 'traditional' structures, while the imperatives of progress were heeded by providing for the development of individuals.
African Studies Seminar series. Paper presented 25 May, 1998
Keywords: Customary law. South Africa; South Africa. Race relations; South Africa. Politics and government. To 1836; South Africa. Politics and government. 1836-1909